An Empiric Evaluation of a Real-Time Robot Dancing Framework based on Multi-Modal Events - João Lobato Oliveira; Luis Paulo Reis; Brigida Monica Faria; Fabien Gouyon (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Musical robots have already inspired the creation of worldwide robotic dancing contests, as RoboCup-Junior's Dance, where school teams, formed by children aged eight to eighteen, put their robots in action, performing dance to music in a display that emphasizes creativity of costumes and movement. This paper describes and assesses a framework for robot dancing edutainment applications. The proposed architecture enables the definition of choreographic compositions, which result on a conjunction of reactive dancing motions in real-time response to multi-modal inputs. These inputs are shaped by three rhythmic events (representing soft, medium, and strong musical note-onsets), different dance floor colors, and the awareness of the surrounding obstacles. This layout was applied to a Lego-NXT humanoid robot, built with two Lego-NXT kits, and running on a hand-made dance stage. We report on an empirical evaluation over the overall robot dancing performance made to a group of students after a set of live demonstrations. This evaluation validated the framework's potential application in edutainment and its ability to sustain the interest of the general audience by offering a reasonable compromise between musical-synchrony, animacy and dance performance’s variability. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1327